Connected lands : new perspectives on ecological networks planning - Schilleci, Filippo, 1963-; Todaro, Vincenzo; Lotta, Francesca (Springer, 2017)
This book explores and outlines the reference theoretical basis of ecological networks within the international debate, focusing on how protected areas should no longer be considered as the sum of different components but rather as a network. The various European, transnational and national models of ecological networks/connections are analyzed on the basis of a detailed, updated study of relevant documents. The complex picture that emerges shows a wide range of reticular-ecological models within European plans and programs, but also many non-integrated experiences. The book subsequently examines the regulation of ecological networks/connections within planning instruments, explaining the critical points and referring to different ecological network models and specific local realities. Lastly, the book addresses two Italian case studies regarding the different normative and planning frameworks, both at a national and regional level, and demonstrating not only how ecological networks/connections can be structured within plans, but also how these networks/connections represent the core element of territory development and preservation. As such, it provides an essential tool for containing habitat fragmentation, offering a new perspective that integrates theoretical approaches and methods with planning models and the lessons learned from local applications.
Keywords: Environmental policy -- Europe.; Urban ecology (Biology); City planning -- Environmental aspects.; Europe.; elektronické knihy; electronic books